Mathematical modelling in economic processes (Journal of Information Technologies in Education (ITE), 2007)
In article are considered a number of methods of mathematical modelling of economic processes and opportunities of use of spreadsheets Excel for reception of the optimum decision of tasks or calculation of financial operations with the help of the built-in functions.